Post-interventional Evaluation and Follow-Up in Children With Patent Ductus Arteriosus Complicated With Moderate to Severe Pulmonary Arterial Hypertension: A Retrospective Study - Rong, Xing; Ye, Qiaofang; Wang, Qiaoyu; Wang, Jiajun; Zhu, Qiongjun; Chen, Youran; Wu, Rongzhou (Frontiers in Cardiovascular Medicine, 2021)
Background: Transcatheter closure is an important treatment for Patent ductus arteriosus (PDA) complicated with middle and severe pulmonary arterial hypertension (PAH). This report presents our experience with transcatheter closure of PDA complicated with middle and severe PAH. Methods: The 49 cases of PDA complicated with middle and severe PAH were collected in the Second Affiliated Hospital and Yuying Children’s Hospital from January 2014 to December 2019 with transcatheter closure of PDA and follow-up. All patients were invited for clinical and transthoracic echocardiography, electrocardiogram, and thoracic radiography check-up. Results: Device implantation was successful in 48 of 49 patients (98.0%). Among them, 30 cases were in the CD (PAH after defect correction) group, and 19 examples were in the NCD (Non-PAH after defect correction) group. Pulmonary systolic pressure, left atrial dimension, and left ventricular end-diastolic dimension immediately after interventional therapy and 6 months later were lower than the preoperative levels (P<0.05). The incidence of immediate residual shunt (RS) in this study was 34.9%, of which the predominantly minimal amount shunt. RS all disappeared in 1 year after therapy. Four patients had thrombocytopenia and one patient has left pulmonary artery stenosis. No other serious adverse event occurred during the follow-up period. The pressure gradient tricuspid valve regurgitation (PGTI) and the right heart catheterization (RHC) consistency points was 93.75 % (15/16) are within the 95% consistency limit by the Bland-Altman method. The Logistic regression analysis was concluded that the preoperative Pp/Ps and the narrowest diameter of PDA are risk factors for postoperative PAH (P<0.05). The cut-off point of the preoperative Pp/Ps and the narrowest diameter of PDA are calculated to be 0.595 and 4.75mm respectively. Conclusion: Interventional occlusion in children with PDA complicated with moderate and severe PAH is safe, effective and with few complications. Targeted drug therapy has good clinical effect. The narrowest diameter of PDA, the preoperative Pp/Ps may be one of the risk factors of residual PAH after interventional therapy.